Pengaruh Propolis Terhadap Il-6 Pada Diabetes Melitus Tipe 2: A Literature Review - Nazula Rahma Shafriani (Universitas Muhammadiyah Purwokerto, 2021)
Type-2 diabetes is a metabolic disease characterized by an increase in blood sugar levels due to decreased insulin secretion by pancreatic beta cells, or inappropriate insulin action. The pathophysiology of type-2 diabetes is related to inflammatory mechanisms caused by an increase in proinflammatory cytokines such as IL-6. Propolis has an anti-inflammatory role that can influence type 2 diabetes. To determine the effect of propolis as an anti-inflammatory to the IL-6 cytokines in type 2 Diabetes Mellitus A Literature review by searching electronic databases on Pubmed, ProQuest, and Google Scholar with the keywords